PERLINDUNGAN HUKUM TERHADAP PIHAK YANG DIRUGIKAN DARI TERJADINYA MISBRUIK VAN OMSTANDIGHEDEN DALAM PERIKATAN - Ayu Maulidia Rahmah (2021)
Misbruik van omstandigheden or abuse of circumstances has occurred in Indonesia. One of the case that contain an abuse of circumtanses is a case between PT. Indosat with PT. LTI. Abuse of circumstances in Indonesia has not been regulated in Indonesia's statutory regulations, where the abuse of circumstances is only regulated in jurisprudence. Of course there is a legal vacuum and results in the absence of legal certainty for the party that is aggrieved from the abuse of circumstances in an agreement. This research aims to determine the misbruik van omstandigheden implications as well as to know the legal protection for the aggrieved party from the occurrence of misbruik van omstandigheden in an engagement. The results of this research indicate that there is a legal vacuum related to the regulation of the abuse of circumstances in Indonesia where the abuse of circumstances is only regulated in jurisprudence. Related to the judge's decision that used as jurisprudence and the validity of the agreement based on the Civil Code, Article 1320, the abuse of the situation is related to the incomplete subjective requirements. Incomplete subjective terms will only result in "canceled" the Agreement.